Antibacterial drugs in products originating from aquaculture: assessing the risks to public welfare - RIGOS, G.; BITCHAVA, K.; NENGAS, I. (Mediterranean Marine Science, 2010)
As aquaculture expands to meet human demand and compensate for pessimistic forecasts of fisheries catches, usage of antibacterial agents to combat or forestall bacterial diseases is still a necessity, although effective vaccines and improved hygiene have aided drastically to this battle. The hazards for the consumer perspective arising from the imprudent use of such chemicals can be detrimental especially if the residues persist above legal tolerance. These may include selection and dissemination of resistant bacteria, disruption of the colonization barrier in the human intestinal flora and allergic reactions. In cases that unlawful drugs reached the consumer via consumption of aquatic products, human health may be jeopardized even further. The present review article assesses these risks on human health.